Konsep An-Nafs dan Ar-Ruh - Al Maududi, Abu A’la; Azzahra, Dini; Siahaan, Mariadina; Harahap, Muhammad Nazarruddin; Putri, Rizky Amaliyah; Lubis, Ramadan (Perkumpulan Manajer Pendidikan Islam Indonesia (PERMAPENDIS) Prov. Sumatera Utara, 2025)
This article aims to examine the concepts of an-nafs (the soul) and ar-r?? (the spirit) in Islamic thought based on the Qur’an and the perspectives of theistic Muslim philosophers, particularly Al-Ghazali and Buya Hamka. The main issue addressed in this study is the conceptual distinction and interrelation between an-nafs and ar-r??, which are often used interchangeably in Islamic discourse. This research employs a qualitative library research method with a descriptive-analytical approach, focusing on Qur’anic verses, classical and modern Qur’anic exegesis, and selected philosophical works. The findings reveal that an-nafs refers to the human self associated with personal identity and moral disposition, possessing tendencies toward piety or deviation, while ar-r?? is understood as a non-physical spiritual essence originating from the divine command of God and serving as the source of life. In Islamic philosophical thought, ar-r?? is regarded as the core of human existence, whereas an-nafs represents its manifestation in interaction with the body and the material world. This study concludes that a clear understanding of the relationship between an-nafs and ar-r?? offers an integrative framework for comprehending the spiritual, moral, and existential dimensions of human beings in Islam.